The Effectiveness of Student Electronic Worksheet-Based on Project-Based Learning to Improve Student Critical Thinking Skills in Green Chemistry Materials - Rewanda, Fania Fasya; Hidayah, Rusly (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Critical thinking skills are essential abilities that students must have to face the challenges of learning in the 21st century. However, the PISA test results in 2022 showed that the critical thinking skills of Indonesian students were still low compared to the average OECD country. This research aims to produce electronic student worksheets based on project-based learning (PjBL) to improve students' critical thinking skills on green chemistry materials. This type of research is development research with a one-group pretest-posttest design and uses the 4D model from Thiagarajan, Semmel, and Semmel’s (1974). This 4D development model consists of four stages: define, design, develop, and disseminate, but is limited to the development stage only. This research was conducted at SMAN 7 Surabaya, with the research subjects being class X-6 students, a total of 28 people. The feasibility of this learning media was reviewed from its effectiveness. The effectiveness was measured through cognitive tests with scores above the learning objective completeness criteria ≥ 75%, which showed a percentage of 100% classical completeness. Effectiveness is also seen from the results of the critical thinking ability test. Critical thinking ability test data was tested with the Shapiro-Wilk normality test and obtained a significance of < 0.05, so further tests were carried out using the Wilcoxon Signed Rank test and obtained a significance of 0.000, which stated that there was a difference between pretest and posttest data. Thus, the learning media developed can be declared effective based on the results of cognitive test data and critical thinking ability test data. Unlike previous studies that focused on creative thinking skills, this study uniquely targets critical thinking skills using PjBL.